First Let we solve the Original system of equations:
equation (1): ![x+3y=5](https://tex.z-dn.net/?f=%20%20x%2B3y%3D5%20)
equation (2): ![7x-8y=6](https://tex.z-dn.net/?f=%207x-8y%3D6%20)
Multiplying equation (1) by 7, we get
![7x+21y=35 -->(3)](https://tex.z-dn.net/?f=%20%207x%2B21y%3D35%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20--%3E%283%29%20)
![7x-8y=6 --> (2)](https://tex.z-dn.net/?f=%20%20%20%20%207x-8y%3D6%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20--%3E%20%282%29%20)
Subtracting,
implies ![y=1](https://tex.z-dn.net/?f=%20y%3D1%20)
Then
Thus the solution of the original equation is![x=2, y=1.](https://tex.z-dn.net/?f=%20%20x%3D2%2C%20y%3D1.%20)
Now Let we form the new equation:
Equation 2 is kept unchanged:
Equation (2):![7x-8y=6](https://tex.z-dn.net/?f=%20%207x-8y%3D6%20)
Equation 1 is replaced with the sum of equation 1 and a multiple of equation 2:
Equation (1): ![8x-5y=11](https://tex.z-dn.net/?f=%208x-5y%3D11%20)
Now solve this two equations: ![8x-5y=11, \\ 7x-8y=6](https://tex.z-dn.net/?f=%208x-5y%3D11%2C%20%5C%5C%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%207x-8y%3D6%20)
Multiply (1) by 7 and (2) by 8,
![56x-35y=77](https://tex.z-dn.net/?f=%20%2056x-35y%3D77%20)
![56x-64y=48](https://tex.z-dn.net/?f=%20%20%2056x-64y%3D48%20)
Subtracting,
implies ![y=1](https://tex.z-dn.net/?f=%20y%3D1%20)
Then x=2.
so the solution for the new system of equation is x=2, y=1.
This Show that the solution to the system of equations 8x − 5y = 11 and 7x − 8y = 6 is the same as the solution to the given system of equations